ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI - RONALDI, HENDRA (Berkala Ilmiah Mahasiswa Akuntansi)
This study is a replication of a study conducted by Soegiharto (2001) and has been modified by researchers. This study aims to analyze the factors that affect the performance of accounting information systems. Factor-factor is defined as follows: user involvement, user capabilities, top management support, the formality of system development, training and user education, information systems control committee, and the influence of the location of the information systems department. This study used purposive sampling techniques in collecting data. Data were collected by distributing questionnaires to 13 companies Taxi in Surabaya where each company deployed 5 questionnaire. Questionnaires were distributed containing the factors that affect the performance of accounting information systems. Data were analyzed using SPSS version 16.0. The analysis showed that top management support, and formalitation of system positive effect the satisfaction of the AIS. Besides user involvement negative effect the satisfaction of the AIS. Formalitation of system also positive affect the use of AIS.